Optimization of the process variables on biodegradable industrial lubricant basestock synthesis from Jatropha curcas seed oil via response surface methodology - Ifeanyi-Nze, Favour Okechi; Akhiehiero, Ejiro Thelma (Frontiers in Energy Research, 2023)
The synthesis of biolubricants from renewable feedstocks is currently gaining attention. Over 95% of the market is comprised of lubricants made from petroleum. Due to their limited biodegradability and high eco-toxicity, lubricants generated from petroleum constitute a significant environmental hazard. As pollution levels increase and oil supplies decline, there is a rising need to develop biobased alternatives. Manufacturing cleaner fuel products will mitigate the negative environmental impact of greenhouse gas emissions, which contribute to global warming. Jatropha curcas seed oil is an efficient renewable feedstock for biolubricant synthesis. This study optimized the process variables on biodegradable lubricant basestock production from J. curcas seed oil. A central composite design was used to maximize the chemical interaction between J. curcas methyl ester and ethylene glycol (EG) as a polyol. A total of 20 experimental runs were done to examine reaction temperature, time, and the ethylene glycol to fatty acid methyl ester (EG-to-FAME) molar ratio. A statistical model indicated that the maximum conversion yield of jatropha biolubricant (JBL) would be 92.48% under the following optimum reaction conditions: 128.95°C, 202.40 min, and ethylene glycol to fatty acid methyl ester (EG-to-FAME) molar ratio of 3.87:1. At these optimum conditions, an average jatropha biolubricant (JBL) yield of 94.12% was achieved under experimental conditions, and this value was well within the range predicted (92.48%) by the model. The quadratic model predicted the biolubricant output (R2 = 0.9919). The synthesized biolubricant met the requirements of Viscosity Grade 46 (ISO VG 46) set by the International Organization for Standardization.